RANCANG BANGUN APLIKASI STOK BARANG BERBASIS WEB MENGGUNAKAN QR DI PT CARMIN - Nur Aprilyani; Pangaribuan, Hotma (Computer Science and Industrial Engineering, 2023)
Technological developments in the era of the industrial revolution 4.0 are very varied and varied for use by humans in carrying out their life activities, one of which is the use of information systems to be able to optimize profit and facilitate performance in carrying out business processes. One implementation of the rapid development of technology is a web application, a website-based application information system which in this study helps PT. Carmin, which is located in the Rapindo Industrial Estate area, is conducting an audit of stock data. In addition to using the web as the operating basis for this design application, it implements a quick response code (QR) to speed up employee performance in inputting stock data into the application database. The design of the inventory application is based on the result of data collection which was carried out of approximately 4 months so that the requirements for the system are defined, namely incoming stock input, outgoing stock input, and incoming QR input. The information system is built using the PHP programming language and utilizes MySQL as a database to make website dynamic. In designing the model used is the waterfall model so that the need analysis process up to the maintenance stage is well defined, the research is refined with research and developments methods so that theoretical and practical benefits can be achieved and in accordance with the initial objectives this information system was designed to help PT. Carmin in conducting inventory audits